Optimal Laboratory Cultivation Conditions of Limnospira maxima for Large-Scale Production - Yirlis Yadeth Pineda-Rodríguez; Diana Sofia Herazo-Cárdenas; Adriana Vallejo-Isaza; Marcelo F. Pompelli; Alfredo Jarma-Orozco; Juan de Dios Jaraba-Navas; Jhony David Cordero-Ocampo; Marianella González-Berrio; Daniela Vegliante Arrieta; Ana Pico-González; Anthony Ariza-González; Katia Aviña-Padilla; et al. (Biology, 2023)
Cultivating Limnospira maxima, renowned for its abundant proteins and valuable pigments, faces substantial challenges rooted in the limited understanding of its optimal growth parameters, associated high costs, and constraints in the procurement of traditional nitrogen sources, particularly NaNO3. To overcome these challenges, we conducted a comprehensive 4 × 3 factorial design study. Factors considered included white, red, blue, and yellow light spectra, along with nitrogen sources NaNO3 and KNO3, as well as a nitrogen-free control, for large-scale implementation. Optimal growth, measured by Optical Density, occurred with white and yellow light combined with KNO3 as the nitrogen source. These conditions also increased dry weight and Chl-a content. Cultures with nitrogen deprivation exhibited high values for these variables, attributed to carbon accumulation in response to nitrogen scarcity. Phycocyanin, a crucial pigment for nutrition and industry, reached its highest levels in cultures exposed to white light and supplemented with KNO3, with an impressive content of 384.11 g kg−1 of dry weight. These results highlight the efficacy and cost-efficiency of using a combination of white light and KNO3 for large-scale L. maxima cultivation. This strategy offers promising opportunities to address global food security challenges and enhance the production of industrially relevant pigments.